Astrocytes spatially restrict VEGF signaling by polarized secretion and incorporation of VEGF into the actively assembling extracellular matrix. Issue 3 (5th November 2015) - Egervari, Kristof; Potter, Gael; Guzman‐Hernandez, Maria Luisa; Salmon, Patrick; Soto‐Ribeiro, Martinho; Kastberger, Birgit; Balla, Tamas; Wehrle‐Haller, Bernhard; Kiss, Jozsef Zoltan
Abstract : The spatial organization of vascular endothelial growth factor (VEGF) signaling is a key determinant of vascular patterning during development and tissue repair. How VEGF signaling becomes spatially restricted and the role of VEGF secreting astrocytes in this process remains poorly understood. Using a VEGF‐GFP fusion protein and confocal time‐lapse microscopy, we observed the intracellular routing, secretion and immobilization of VEGF in scratch‐activated living astrocytes. We found VEGF to be directly transported to cell‐extracellular matrix attachments where it is incorporated into fibronectin fibrils. VEGF accumulated at β1 integrin containing fibrillar adhesions and was translocated along the cell surface prior to internalization and degradation. We also found that only the astrocyte‐derived, matrix‐bound, and not soluble VEGF decreases β1 integrin turnover in fibrillar adhesions. We suggest that polarized VEGF release and ECM remodeling by VEGF secreting cells is key to control the local concentration and signaling of VEGF. Our findings highlight the importance of astrocytes in directing VEGF functions and identify these mechanisms as promising target for angiogenic approaches. GLIA 2016;64:440–456 Main points: Astrocytes target VEGF to integrin‐mediated cell‐matrix adhesions and promote local VEGF immobilization by matrix remodeling. Pericellular immobilization directs VEGF‐signaling, and leads to an autocrine inhibition of adhesion turnover.